2023
DOI: 10.4103/aja2022108
|View full text |Cite
|
Sign up to set email alerts
|

The safety of radium-223 combined with new-generation hormonal agents in bone metastatic castration-resistant prostate cancer: a systematic review and network meta-analysis

Abstract: Patients with bone metastatic castration-resistant prostate cancer (mCRPC) might benefit from radium-223 (223Ra) combined with new-generation hormonal agents (NHAs) in terms of survival and quality of life (QoL). However, the safety of combination therapies remains unclear. Therefore, we aimed to perform a network meta-analysis by reviewing the literature about the combination of 223Ra with abiraterone acetate plus prednisone (AAP) or enzalutamide and to evaluate the safety of combination therapy in bone mCRPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…22,23 However, other studies and meta-analyses indicate that the combination of radium-223 and AR-targeted therapy is effective, and the risk of fracture can be reduced by concomitant use of BHAs such as denosumab or zoledronic acid. [24][25][26][27][28][29][30][31] The ongoing…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, other studies and meta-analyses indicate that the combination of radium-223 and AR-targeted therapy is effective, and the risk of fracture can be reduced by concomitant use of BHAs such as denosumab or zoledronic acid. [24][25][26][27][28][29][30][31] The ongoing…”
Section: Discussionmentioning
confidence: 99%
“…The ERA‐223 study indicated increased risk of fracture when abiraterone acetate and radium‐223 were used together versus abiraterone alone, 21 resulting in regulatory restrictions on this combination 22,23 . However, other studies and meta‐analyses indicate that the combination of radium‐223 and AR‐targeted therapy is effective, and the risk of fracture can be reduced by concomitant use of BHAs such as denosumab or zoledronic acid 24–31 . The ongoing phase 3 PEACE III study (NCT02194842) will assess the efficacy and safety of radium‐223 combined with enzalutamide.…”
Section: Discussionmentioning
confidence: 99%